Shifts in Plant Community Assembly Processes across Growth Forms along a Habitat Severity Gradient: A Test of the Plant Functional Trait Approach - Xu, Jinshi; Chai, Yongfu; Wang, Mao; Dang, Han; Guo, Yaoxin; Chen, Yu; Zhang, Chenguang; Li, Ting; Zhang, Lixia; Yue, Ming (Frontiers in Plant Science, 2018)
Species respond to changes in their environments. A core goal in ecology is to understand the process of plant community assembly in response to a changing climate. Examining the performance of functional traits and trait-based assembly patterns across species among different growth forms is a useful way to explore the assembly process. In this study, we constructed a habitat severity gradient including several environment factors along a 2300 m wide elevational range at Taibai Mountain, central China. Then we assessed the shift on functional trait values and community assembly patterns along this gradient across species among different growth forms. We found that 1) although habitat-severity values closely covaried with elevation in this study, an examined communities along a habitat severity gradient might reveal community dynamics and species responses under future climate change. 2) the occurrence of trait values along the habitat severity gradient across different growth forms were similar, whereas the assembly pattern of herbaceous species was inconsistent with the community and woody species. 3) the trait-trait relationships of herbaceous species were dissimilar to those of the community and woody species. These results suggest that 1) community would re-assemble along habitat severity gradient through environmental filtering, regardless of any growth forms and that 2) different growth forms' species exhibiting similar trait values' shift but different trait-trait relationship by different trait combinations.